Soil nematode responses to fertilization with ammonium nitrate after six years of unfertilized apple orchard - Azpilicueta, Claudia V.; Aruani, M. Cristina; Chaves, Eliseo; Reeb, Pablo D. (Spanish Journal of Agricultural Research, 2014)
A nematode community was used as a bioindicator of changes in agroecosystems caused by fertilization. The effect of applying nitrogen (N) fertilizer on a soil nematode community structure was studied in a soil which had not been fertilized for six years in the Rio Negro Valley, Argentina. Treatments were: i) 100 kg N ha-1 (N100); ii) 200 kg N ha-1 (N200); in each case 50% of the dosage was applied at the time of petal fall and 50% at fruit harvest in 2004/2005, 2005/2006, 2006/2007 growing seasons; and iii) control with no fertilizer (N0). Soil samples were collected in the 0 to 30 cm soil layer in October, November, April and July in each growing season. The number of bacterivores increased in N200 compared to N0. Cephalobidae were present in greater numbers in N200 than in N100 and N0. Predator abundance was lower under N200, after the first N application in each growing season. The ratio of fungivores to bacterivores (F/B) was 0.21, 0.3 and 0.41 in N200, N100 and N0, respectively. N200 resulted in a community with a lower maturity index (MI) than N0. Structure index (SI) was lower in N200 than N100 and N0. The enrichment index (EI) was less sensitive at detecting fertilizer effects. In November and April, soil nitrate concentrations were higher in N200 than in N100 and N0. Soil nitrate concentration was positively correlated with EI and negatively with MI, SI and F/B. N200 affected the trophic structure of the nematode community consistent with a less stable soil system.